Upaya Meningkatkan Motivasi Belajar Peserta Didik Menggunakan Permainan Pada Materi Bola Tangan Kelas VII E di SMPN 1 Waru Tahun Pelajaran 2024/2025 - Hermin Adi Bakhrudin; Nanik Indahwati; Demy Ilmiawan (Journal of Creative Student Research, 2024)
This Classroom Action Research (CAR) is a form of reflective research by teachers to improve the learning motivation of students under their responsibility. This classroom action research involves 2 cycles, the first cycle uses several stages, including planning, implementation, observation, and reflection. The next second cycle is expected to increase learning motivation from the previous cycle. The results of the study showed that cycle I received an assessment percentage of 88%, while cycle II experienced an increase of 92%, and both cycles received very good criteria. Although the criteria got the same results, the average percentage showed an increase in student motivation, indicating that there was a change for the better after handball game learning was carried out in cycle II.